Peranan Persepsi Manfaat sebagai Mediasi dalam Pengaruh Kemudahan Penggunaan dan Kepercayaan terhadap Penggunaan E-Commerce pada Aplikasi Traveloka - Aziziyah Aziziyah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
As time went on, business development also grew more rapidly. Booking and travel tickets online compliment online marketing. The aims to provide perceived ease of use, perceived usefulness, and trust in consumers to influence the system's level of use at higher consumers. The purpose of this study is to analyze and discuss the effect of perceived ease of use, perceived usefulness, and trust in e-commerce usage. Respondents in this study are consumers who have booked aeroplane tickets in less than one year with a minimum age of 18 years. The sampling method is non-probability sampling, and the sampling technique uses judgmental sampling. The sample used was 220. The data collection technique used in this study was an online questionnaire. Data analysis techniques using path analysis with the AMOS program. This study indicates that perceived ease of use has a positive and significant effect on perceived usefulness. Perceived ease of use has a positive and significant effect on e-commerce. Perceived benefits have a positive and significant effect on the use of e-commerce. Furthermore, trust has a positive and significant effect on the use of e-commerce.